Exploring older people’s experiences of ageing in place: a scoping review / Noorlailahusna Mohd Yusof and Dr. Suziana Mat Yasin - Mohd Yusof, Noorlailahusna; Mat Yasin, Suziana (Universiti Teknologi MARA, Kedah, 2023)
The literature on the concept of ageing in place covers a wide range of areas. However, there is a shortage of studies on how it should be described according to older people's lived experiences. This scoping review methodology provides a five-step framework aimed at addressing the knowledge gap by exploring older people’s lived experiences of ageing in place. Two databases, Web of Science (WoS) and Scopus, were used to search for relevant literature, and eleven articles were selected. 571 quotations from eleven studies described older people’s (aged 60 to 99 years) experiences of ageing in place. Older people’s favourable and less favourable experiences of ageing in place were of anything related to the built and social environments. So long as their needs are fulfilled, they are happy to age in place. Otherwise, they would feel burdened to remain and would consider relocating or moving from their homes and community. Overall, understanding the matters related to ageing in place made older people satisfied and contributed to their quality of life. Therefore, the stakeholders must collaborate and cooperate in creating an environment that can accommodate the needs of older people.